Using the Riddle Technique To Increase Students’ Vocabulary Mastery At Grade IX Of SMPN 1 Bengkulu - Lorenza, Oktazsya Marjelina; Ristiyanti, Surya Hazar; Puspita, Hilda (UNIB Press, 2024)
This study aimed to determine if using the riddle technique would enhance a student's vocabulary and response after using it. Classroom action research (CAR) was used. Grade IX.1 of SMPN 1 Bengkulu City, consisting of 34 students, was the subject of this study. There were two cycles in this research. The analysis of the observation checklists, field notes, and questionnaires has yielded qualitative data. In addition, quantitative data have been obtained on the students' pretest, post-test 1, and post-test 2 scores. Results show that students learn vocabulary more effectively using the riddle technique. It can be noted that the student score has improved. The student's average score on the pretest was 61.6, the average score for post-test one cycle 1 was 73.3, and the average for post-test 2 was 85.9. Furthermore, the questionnaire showed that students were interested and motivated in teaching and learning while implementing the Riddle game. Most students thought using riddles was an outstanding way to improve their language skills. The students were interested in learning vocabulary through riddles and agreed they could improve their language skills.